Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Terhadap Motivasi Belajar Matematika Siswa Kelas IV MI The Noor Bendunganjati Pacet Mojokerto - Sri Handayani (LP3M IAI Al Urwatul Wutsqo Jombang, 2022)
Teams Games Tournament Model, Learning Motivation The teaching and learning process carried out by teachers at MI The Noor school, especially in the use of learning models is still very lacking, this is evidenced by the learning outcomes of students who are still much below the KKM, besides that when the teaching and learning process is carried out, students are less enthusiastic in following the lesson. this greatly affects the desired understanding. Therefore, the learning process must be able to choose the right learning model, the Teams Games Tournament type cooperative learning model is very suitable for use in learning, because the Teams Games Tournament type cooperative learning model can arouse the enthusiasm of students in the learning process, This study aims to determine the effect of using the Teams Games Tournament type of cooperative learning model on the learning motivation of fourth grade students in the Circumference and area of square, rectangular, and triangular shapes. The research design is One Group Pretest Posttest. The research population consisted of 88 students in class I, II, III, IV, V. VI and 20 students in class IV as samples. The results of data analysis using the Paired sample t-test test obtained the value of Sig. (2-tailed) of 0.000, which means that the test results obtained a value smaller than 0.05, so it can be concluded that there is an influence in the use of the Teams Games Tournament type of cooperative learning model on students' learning motivation